Teaching Vocabulary to Beginners Through a Contextual Approach - M. Rizal Rizqi (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
The aims of this study are twofold. First, this study aims to develop vocabulary learning materials based on a contextual approach for the students of “Fadllillah”. Second, it aims to examine the effectiveness of the developed vocabulary learning materials. The development of this textbook was motivated by the fact that vocabulary instruction at “Fadllillah” had long relied on Durus al-Lughah; however, its use had not sufficiently improved students’ learning achievement or increased their interest in learning. This study employed a Research and Development (R&D) method based on the Borg and Gall model. The procedures included research and information gathering, planning, developing the preliminary product, validation testing, field testing, product revision, and final product revision. The results of this study show two major findings. First, the developed learning materials have several characteristics: they are specifically designed for beginner learners of Arabic, easy to memorize and understand, and practical to use in conversations related to daily activities. The examples, exercises, and presentation of the materials are systematically arranged from simple to more complex topics. In addition, the materials employ an interactive presentation method that encourages active learning. Various colors and illustrations are also included to help students understand the content more easily. Second, the use of the developed vocabulary learning materials effectively improved students’ vocabulary learning outcomes and increased their learning interest. This effectiveness was indicated not only by the differences in achievement scores between the control group and the experimental group, as analyzed using SPSS version 22, but also by the questionnaire results, which showed that the learning materials were easy to understand and attracted students to read and learn with greater enthusiasm. The results of this study indicate that students showed greater interest in learning vocabulary than before. Consequently, they were able to understand the learning materials more easily through the use of vocabulary learning materials developed based on a contextual approach.